Anti-cancer Effect of Luminacin, a Marine Microbial Extract, in Head and Neck Squamous Cell Carcinoma Progression via Autophagic Cell Death - Shin, Yoo Seob (Cancer Res Treat, 2016)
PURPOSE: The purpose of this study is to determine whether luminacin, a marine microbial extract from the Streptomyces species, has anti-tumor effects on head and neck squamous cell carcinoma (HNSCC) cell lines via autophagic cell death. MATERIALS AND METHODS: Inhibition of cell survival and increased cell death was measured using cell viability, colony forming, and apoptosis assays. Migration and invasion abilities of head and cancer cells were evaluated using wound healing, scattering, and invasion assays. Changes in the signal pathway related to autophagic cell death were investigated. Drug toxicity of luminacin was examined in in vitro HaCaT cells and an in vivo zebrafish model. RESULTS: Luminacin showed potent cytotoxicity in HNSCC cells in cell viability, colony forming, and fluorescence-activated cell sorting analysis. In vitro migration and invasion of HNSCC cells were attenuated by luminacin treatment. Combined with Beclin-1 and LC3B, Luminacin induced autophagic cell death in head and neck cancer cells. In addition, in a zebrafish model and human keratinocyte cell line used for toxicity testing, luminacin treatment with a cytotoxic concentration to HNSCC cells did not cause toxicity. CONCLUSION: Taken together, these results demonstrate that luminacin induces the inhibition of growth and cancer progression via autophagic cell death in HNSCC cell lines, indicating a possible alternative chemotherapeutic approach for treatment of HNSCC.